Patronase dan Nepotisme Pada Pengelolaan Pariwisata: Studi Pada Desa Wisata Bira Tengah Kabupaten Sampang - Arrozi, Hidayatullah; Ahimsa-Putra, Heddy Shri; Widyaningsih, Yulia Arisani (Pusat Studi Pariwisata Universitas Gadjah Mada, 2025)
Tourism development in villages can bring wealth. But rural elites use it to keep their power. This is the case in Desa Wisata Bira Tengah, Sampang Regency. The headman has strong influence in tourism at a village-owned enterprise (VOE). He does this by empowering his clients and placing his core kin in key positions. This study aims to: (1) analyze patronage and nepotism in tourism management at Desa Wisata Bira Tengah, Sampang Regency and (2) assess the impact of patronage and nepotism on tourism management. This study uses a qualitative approach. It collects data via literature studies, interviews, observations, and documents. The technique for selecting research subjects is purposive sampling. This study applies Spradley's ethnographic approach as a data analysis method. The study found that patronage occurred between the headman and the VOE director as patrons, with the employees as clients. Patrons use their authority on VOE to help clients. They provide access to work in tourism and to protection. Clients repay by backing the patron in conflicts and politics. The headman places his core kin in these roles: director VOE, head of the tourism unit, head of the Tourism Awareness Group (Pokdarwis), and secretary and treasurer. Patronage and nepotism have downsides. They weaken accountability and transparency, reduce employee initiative, and create exclusivity. The positive impact that has emerged is to make the team solid.